2008
DOI: 10.1093/alcalc/agn044
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism in Ethanol-Treated Rat Pups and Adults: Effects of Folic Acid

Abstract: Despite the fact that alcohol intake provokes different lipid alterations in adults and in pups whose mothers drank ethanol, folic acid contributes to the alleviation of these adverse effects reducing HMG-CoA reductase activity in adult rats and, except BA levels, to normalizing lipids values due to the fact that folic acid acts as a choleretic compound. We can therefore assume that folic acid supplementation reduces alcohol-induced hypercholesterolaemia by decreasing synthesis and increasing catabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
1
25
2
Order By: Relevance
“…As GPx4 acts protecting against oxidation of the membrane phospholipids, it could play an important role during lactation (when there is an intense phase of cell formation), protecting the newly synthesized phospholipids. Taking into account that in this period of life the amount of phospholipid vs triglycerides is higher, the lipid profile is different to that found in adulthood (Ojeda et al 2008); the increase in GPx4 could be related to the absence of lipid oxidation in the groups studied. Based on this information, it can be concluded that GPx1 is very sensitive, and GPx4 is highly resistant, to dietary Se deficiency in offspring, and according to this, as GPx1 expression is fully committed, in SD pups protein oxidation occurs; however, as GPx4 expression is not completely decreased, phospholipid Selenium and development in pups oxidation does not take place.…”
Section: Selenoprotein Expressionmentioning
confidence: 58%
“…As GPx4 acts protecting against oxidation of the membrane phospholipids, it could play an important role during lactation (when there is an intense phase of cell formation), protecting the newly synthesized phospholipids. Taking into account that in this period of life the amount of phospholipid vs triglycerides is higher, the lipid profile is different to that found in adulthood (Ojeda et al 2008); the increase in GPx4 could be related to the absence of lipid oxidation in the groups studied. Based on this information, it can be concluded that GPx1 is very sensitive, and GPx4 is highly resistant, to dietary Se deficiency in offspring, and according to this, as GPx1 expression is fully committed, in SD pups protein oxidation occurs; however, as GPx4 expression is not completely decreased, phospholipid Selenium and development in pups oxidation does not take place.…”
Section: Selenoprotein Expressionmentioning
confidence: 58%
“…We found the highest serum GPx activity in AFSO. It seems that folic acid acts synergetically with selenium to increase serum GPx activity, especially during alcohol consumption (where serum basal folic acid concentration decreases) (Ojeda et al, 2008). Possibly, the greatest increase in serum Se was provoked by Se-only supplementation to ethanolexposed rats' pups, something reflected in an increase in Selenoprotein P, the main serum Se transporters (Hollenbach et al, 2008), nor in GPx.…”
Section: Discussionmentioning
confidence: 99%
“…Male (n 5 6) and female (n 5 6) rats were mated to obtain the 1st-generation offspring for each group. After reproduction, pregnant rats were housed individually in plastic cages, and continued their chronic ethanol treatment until the end of the lactation period, so alcohol was supplied to mothers for 13 weeks (induction, reproduction, gestation, and lactation periods) (Ojeda et al, 2008). The day of parturition was designated as day 1 of lactation, the number of offspring being reduced to 10 per mother at parturition, and day 21 designated as the final day of the lactation period.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the highest affinity found in the AFS offspring could be explained by an extra protective effect of folic acid on lipid membranes. Ojeda et al (2008) [20] demonstrated different lipid alterations in adults and in pups whose dams consumed ethanol and that folic acid contributes to alleviation of the adverse effects in these cases. Se-Met absorption was lower in all the control groups studied compared with their alcohol counterparts, probably because paracellular absorption is reduced, since Se-Met, in terms of absorption, acts as an amino acid.…”
Section: Duodenal Absorption Of Selenomethioninementioning
confidence: 99%